PREVEntion and regReSsive Effect of weight-loss and risk factor modification on Atrial Fibrillation: the REVERSE-AF study. Issue 12 (14th June 2018) - Middeldorp, Melissa E; Pathak, Rajeev K; Meredith, Megan; Mehta, Abhinav B; Elliott, Adrian D; Mahajan, Rajiv; Twomey, Darragh; Gallagher, Celine; Hendriks, Jeroen M L; Linz, Dominik; McEvoy, R Doug; Abhayaratna, Walter P; et al.
Abstract: Aims: Atrial fibrillation (AF) is a progressive disease. Obesity is associated with progression of AF. This study evaluates the impact of weight and risk factor management (RFM) on progression of the AF. Methods and results: As described in the Long-Term Effect of Goal-Directed Weight Management in an Atrial Fibrillation Cohort: A Long-Term Follow-Up (LEGACY) Study, of 1415 consecutive AF patients, 825 had body mass index ≥ 27 kg/m 2 and were offered weight and RFM. After exclusion, 355 were included for analysis. Weight loss was categorized as: Group 1 (<3%), Group 2 (3–9%), and Group 3 (≥10%). Change in AF type was determined by clinical review and 7-day Holter yearly. Atrial fibrillation type was categorized as per the Heart Rhythm Society consensus. There were no differences in baseline characteristic or follow-up duration between groups ( P = NS). In Group 1, 41% progressed from paroxysmal to persistent and 26% from persistent to paroxysmal or no AF. In Group 2, 32% progressed from paroxysmal to persistent and 49% reversed from persistent to paroxysmal or no AF. In Group 3, 3% progressed to persistent and 88% reversed from persistent to paroxysmal or no AF ( P < 0.001). Increased weight loss was significantly associated with greater AF freedom: 45 (39%) in Group 1, 69 (67%) in Group 2, and 116 (86%) in Group 3 ( P ≤ 0.001). Conclusion: Obesity is associated with progression of the AF disease. This study demonstrates the dynamic relationship between weight/risk factors and AF. Weight-loss management and RFM reverses the type and natural progression of AF.